Redesign Papan Tulis dengan Prinsip Ergonomi pada Ruangan Kelas Bimbel RHC - Ricky; Oscar Nemesis; Maria Septi Anggraini; Andri Wibowo; Eugenius Rudolfo Legi; Luther Kevas (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2020)
Bimbel RHC is a tutoring service that provides science tutoring services for high school students. Bimbel is located on Bangau Street No.1073, Palembang, South Sumatra. In its effort to progress and develop, besides prioritizing the interests of RHC tutoring students, it also seeks to improve the comfort of teachers. During this time the working conditions of existing teachers are less comfortable for teachers, resulting in musculoskeletal disorder. The problem that occurs is the use of blackboards by people of different height, resulting in bad posture such as bending and tiptoeing. Long removal time can also make you tired on the arm. The method used is the calculation of anthropometry and ergonomics. From the data processing and analysis, an ergonomic whiteboard design with eraser that is united with the whiteboard and height adjustable features is obtained where the maximum height is 211 cm.